Hsp70 protects from stroke in atrial fibrillation patients by preventing thrombosis without increased bleeding risk†. Issue 3 (14th March 2016) - Allende, Mikel; Molina, Eva; Guruceaga, Elisabet; Tamayo, Ibai; González-Porras, José Ramón; Gonzalez-López, Tomás José; Toledo, Estefanía; Rabal, Obdulia; Ugarte, Ana; Roldán, Vanesa; Rivera, José; Oyarzabal, Julen; et al.
Abstract: Aims: Atrial fibrillation (AF) is a major risk factor for cardio-embolic stroke. Anticoagulant drugs are effective in preventing AF-related stroke. However, the high frequency of anticoagulant-associated major bleeding is a major concern. This study sought to identify new targets to develop safer antithrombotic therapies. Methods and results: Here, microarray analysis in peripheral blood cells in eight patients with AF and stroke and eight AF subjects without stroke brought to light a stroke-related gene expression pattern. HSPA1B, which encodes for heat-shock protein 70 kDa (Hsp70), was the most differentially expressed gene. This gene was down-regulated in stroke subjects, a finding confirmed further in an independent AF cohort of 200 individuals. Hsp70 knock-out mice subjected to different thrombotic challenges developed thrombosis significantly earlier than their wild-type (WT) counterparts. Remarkably, the tail bleeding time was unchanged. Accordingly, both TRC051384 and tubastatin A, i.e. two Hsp70 inducers via different pathways, delayed thrombus formation in WT mice, the tail bleeding time still being unaltered. Most interestingly, Hsp70 inducers did not increase the bleeding risk even when aspirin was concomitantly administered. Hsp70 induction was associated with an increased vascular thrombomodulin expression and higher circulating levels of activated protein C upon thrombotic stimulus. Conclusions: Hsp70 induction is a novel approach to delay thrombus formation with minimal bleeding risk, and is especially promising for treating AF patients and in other situations where there is also a major bleeding hazard.